2015
DOI: 10.1111/1365-2656.12415
|View full text |Cite
|
Sign up to set email alerts
|

Time‐scale dependency of host plant biomass‐ and trait‐mediated indirect effects of deer herbivory on a swallowtail butterfly

Abstract: Despite recent attempts to quantify the relative strength of density- and trait-mediated indirect effects, rarely has the issue been properly addressed at the population level. Most research is based on short-term small-scale experiments in which behavioural and/or physiological responses prevail. Here, we estimated the time-scales during which density- and trait-mediated effects manifest, as well as the strength of these effects, using an interaction chain with three organisms (deer-plant-butterfly). A hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It also compliments other work that has demonstrated deer-induced changes to plant community composition can lead to impacts on the insect community (Kanda et al 2005). In contrast, the effect of plant traits was detrimental to insect herbivory, indicating that deer can indirectly alter plant traits, which leads to changes in insect herbivory (Takagi and Miyashita 2015). Furthermore, the path model revealed that soil properties had a net negative (albeit weak) effect on insect herbivory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also compliments other work that has demonstrated deer-induced changes to plant community composition can lead to impacts on the insect community (Kanda et al 2005). In contrast, the effect of plant traits was detrimental to insect herbivory, indicating that deer can indirectly alter plant traits, which leads to changes in insect herbivory (Takagi and Miyashita 2015). Furthermore, the path model revealed that soil properties had a net negative (albeit weak) effect on insect herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the absence of deer herbivory typically leads to increased foliar nutrient concentrations (Lind et al 2012), lower leaf toughness (Coley 1983; Lambers and Poorter 1992) and decreased plant defense (Shikata et al 2013), which is favorable to insect herbivores (Lind et al 2012; Takagi and Miyashita 2015); (2) more S. palmata individuals per area as the result of deer absence (Nishizawa et al 2016) will dilute the increase in insect herbivory, leading to lower insect herbivory per plant; (3) damage by different insect-feeding guilds to S. palmata will be affected differently by sika deer grazing due to disparate resource requirements between guilds (i.e., specialist versus generalist herbivores) (Barrett and Stiling 2007); (4) the functional relationships between soil properties, the plant community and the traits of S. palmata will be altered due to deer exclosure, thereby impacting on insect herbivory. This is because deer presence is known to alter plant traits (Karban 2011; Ohgushi 2005), soil properties (Abbas et al 2012; Kardol et al 2014) and the understory plant community (Nishizawa et al 2016; Takatsuki and Itô 2009; Wardle et al 2001) in ways that can drive insect herbivory via indirect trophic interactions (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of the previous studies have been conducted under spatially (e.g., in the laboratory or mesocosms) and/ or temporally (from days to weeks) limited experimental conditions. In response to the spatial issue, several studies have attempted to quantify indirect interactions in experiments with little or no spatial limitations (Trussell et al 2002, 2004, Wada et al 2013, 2015, Takagi and Miyashita 2015. For instance, Trussell (2011, 2014) showed that the strengths of the antipredator responses of prey varies according to spatial and temporal variation in the predation risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although theoretical studies have suggested the importance of evaluating the long-term dynamics of DMIIs and TMIIs (McPeek and Peckarsky 1998, Luttbeg et al 2003, Abrams 2008, empirical studies are still scarce (Takagi and Miyashita 2015). Previous long-term studies have focused on TMIIs only (Raimondi et al 2000), examined species interactions without distinguishing between DMIIs and TMIIs (e.g., Paine 1966, Fletcher 1987, Wootton 1992 for intertidal rocky shore) or were conducted with spatial limitations (Hoverman andRelyea 2012, Manzur et al 2014).…”
Section: Introductionmentioning
confidence: 99%